2023
DOI: 10.1101/2023.01.26.525749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-4 downregulates BCL6 to promote memory B cell selection in germinal centers

Abstract: Germinal center (GC)-derived memory B cells (MBCs) are critical for humoral immunity as they differentiate into protective antibody-secreting cells during re-infection. GC formation and cellular interactions within the GC have been studied in detail, yet the exact signals that allow for the selection and exit of MBCs are not understood. We show that IL-4 can trigger GC B cell selection and exit by inducing the negative autoregulation of BCL6, the primary GC transcription factor. High affinity/avidity GC B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In the present work investigating how IL-4Rα blockade impacts the B cell repertoire beyond avoidance of IgE production, we found that loss of IL-4/IL-13 signaling in vivo broadly suppresses gene expression, particularly relating to metabolic processes and BCR signaling. Intriguingly, Ag re-exposure could still elicit Ag-specific GC activity in the absence of IL-4/IL-13, an issue which has remained contentious ( 27 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work investigating how IL-4Rα blockade impacts the B cell repertoire beyond avoidance of IgE production, we found that loss of IL-4/IL-13 signaling in vivo broadly suppresses gene expression, particularly relating to metabolic processes and BCR signaling. Intriguingly, Ag re-exposure could still elicit Ag-specific GC activity in the absence of IL-4/IL-13, an issue which has remained contentious ( 27 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…While B-cell-directed therapies inherently impact B cells, it is intriguing that the interleukin-4 receptor (IL-4R) blockade, initially not designed to specifically target B cells, has emerged as a potential regulator of B cell responses and humoral immunity ( 76 , 146 149 ) ( Figure 2B ).…”
Section: Current Therapeutics For Inflammatory Skin Diseases and Pote...mentioning
confidence: 99%
“…This assumption allows activated B cells to remain within the GC, preventing them from exiting GC and becoming MBC. To bridge the gap between these conflicting conclusions on whether IL-4 promotes or inhibit MBC differentiation, a recent study has proposed a plausible explanation ( 149 ). They demonstrated that IL-4 can prompt GC B cell selection and exit through differential regulation of BCL6 expression, depending on the preexisting levels of BCL6 in a given cell.…”
Section: Current Therapeutics For Inflammatory Skin Diseases and Pote...mentioning
confidence: 99%
“…Interestingly, FDC can limit GC IL-4 availability through IL-4Ra expression, enhancing memory B cell generation ( 50 ). IL-4 also triggers a negative autoregulatory mechanism of Bcl6 expression in GC B cells, although it initially enhances Bcl6 in naive B cells to facilitate the generation of GC ( 51 ). This reduction in Bcl6 by IL-4 contributes to a selective process: pre-memory GC B cells with access to supplementary survival signals are granted permission to exit the GC, while those devoid of such signals undergo apoptosis ( 51 ).…”
Section: Cytokines Produced By Tfh and Their Regulationmentioning
confidence: 99%
“…IL-4 also triggers a negative autoregulatory mechanism of Bcl6 expression in GC B cells, although it initially enhances Bcl6 in naive B cells to facilitate the generation of GC ( 51 ). This reduction in Bcl6 by IL-4 contributes to a selective process: pre-memory GC B cells with access to supplementary survival signals are granted permission to exit the GC, while those devoid of such signals undergo apoptosis ( 51 ). These findings suggest that IL-4 acts on B cell differentiation at multiple stages, including GC B cell and memory B cell differentiation.…”
Section: Cytokines Produced By Tfh and Their Regulationmentioning
confidence: 99%